Pre-Monsoon Rain and Its Relationship with Monsoon Onset over the Indochina Peninsula - Kiguchi, Masashi; Matsumoto, Jun; Kanae, Shinjiro; Oki, Taikan (Frontiers in Earth Science, 2016)
We analyzed rainfall during the pre-monsoon season from 1979 to 2002 over the Indochina Peninsula. Our multi-year analysis confirmed that the passage of the upper trough and moisture convergence in the lower troposphere produce intermittent rainfall events during the pre-monsoon season. From this result, three questions are raised. First, what are the characteristics of the upper trough? Second, what is the cause of the significant amount of moisture during the pre-monsoon season over inland Indochina? Third, what is the relationship between the intermittent pre-monsoon rainfall and monsoon onset? Our study suggests the following answers to these questions: 1) The upper trough is associated with the cyclone over the Yangtze River basin. This cyclone is baroclinic, so the upper trough over the study area is produced by the mid-latitude regime. 2) A significant amount of moisture over the Indochina Peninsula is produced by both intermittent rainfall associated with the passage of the upper trough and continuous rainfall occurred over a wide region associated with the equatorial southwesterly. 3) We found no clear relationship between rainfall amount during the pre-monsoon period and timing of monsoon onset over the Indochina Peninsula.